Atypical energetic and kinetic course of excited-state intramolecular proton transfer (ESIPT) in room-temperature protic ionic liquids - Manna, Arpan; Sayed, Mhejabeen; Kumar, Anil; Pal, Haridas (Journal of Physical Chemistry B, 2014)
The excited-state intramolecular proton-transfer (ESIPT) process in 1,8-dihydroxyanthraquinone (18DHAQ) dye has been investigated in protic ionic liquid (PIL) solvents using photochemical measurements. The results demonstrate noteworthy modulations in both steady-state and time-resolved emission characteristics of excited normal (N*) and tautomeric (T*) forms of the dye. That the emission of T* increases unexpectedly upon increasing solvent viscosity indicates that subsequent to the initial forward ESIPT, there is also a relatively slower back ESIPT process involved for the excited dye. It is inferred that the propensity of this back ESIPT process is determined by the dynamics of the diffusive solvent relaxation, a process that is known to be strongly viscosity-dependent in ionic liquids. Evidence of both forward and back ESIPT for the dye has been obtained from femtosecond fluorescence up-conversion measurements. While an unusually fast forward ESIPT is clearly observed in all of the PILs studied, the uncommon back ESIPT process is distinctly indicated in PIL solvents having lower viscosities, certainly due to reasonably fast diffusive solvent relaxation in these solvents that causes a temporal modulation in the energies of the normal and tautomeric forms within a reasonably short time and thereby brings down the energy of N* compared to that of T*, triggering the back ESIPT process. Observation of solvent-viscosity-dependent back ESIPT is an intriguing finding for the present study as to the best of our knowledge, such a behavior has so far not been reported in the literature for the ESIPT reaction.

Observation of the marcus inverted region for bimolecular photoinduced electron-transfer reactions in viscous media - Kumbhakar, Manoj; Manna, Arpan; Sayed, Mhejabeen; Kumar, Anil; Pal, Haridas (Journal of Physical Chemistry B, 2014)
The general observation of Marcus inverted region (MIR) for bimolecular electron-transfer (ET) reactions in different viscous media, e.g., micelles, reverse micelles, vesicles, ionic liquids, DNA scaffold, etc. has been doubted in some recent publications arguing limitations in SternVolmer (SV) analysis to account for the static and transient stages of quenching in these slow diffusing media. Thus, following a theoretical treatment based on a spherically symmetric diffusion equation coupled with conventional Marcus ET description, it has been suggested that the MIR observed in viscous media arises due to the inadequate consideration of different quenching regimes and also due to the differential excited-state lifetimes of the fluorophores used than a genuine one (J. Am. Chem. Soc. 2012, 134, 11396). However, the overall treatment in this study is severely compromised by setting the minimum solvent reorganization energy (?s) to (lambda) to similar to 0.96 eV while fitting the experimental data, which unambiguously suggests that the inversion in ET rate will never appear in the exergonicity (-Delta G(0)) range of 0.16 to 0.71 eV, as is the case for the studied ET systems. Besides, the applicability of the conventional Marcus ET model (instead of Sumi-Marcus two-dimensional ET model) in such extremely viscous media with exceptionally slow solvent response is highly debatable and perhaps is the main cause of the failure in fitting the experimental data quite satisfactorily. In the present study involving ultrafast ET quenching for coumarin derivatives by dimethylaniline donor in viscous ionic liquid media, we demonstrate clear MIR for the intrinsic ET rates, directly obtained from the ultrafast decay components of 110 ps, a time scale in which diffusion of reactants is negligible and the ET rates are either faster than or, at the most, competitive with the solvent reorganization. The appearance of MIR at ?Delta G(0) similar to-0.5 eV, significantly lower than expected from the lambda(s) value, further substantiate the nonapplicability of conventional ET description but certainly advocate for the applicability of the SumiMarcus two-dimensional ET model in such media. Moreover, no obvious correlation has experimentally been observed between the excited-state lifetimes of the coumarin derivatives and the ET rates for a large number of dyes used in the present study. On the basis of the present results and drawing inferences from reported literatures in viscous media, we conclude that not only is the appearance of MIR very genuine but also the mechanistic model necessary to account the observed facts for the bimolecular ET reactions in a viscous medium is the two-dimensional ET description, which deals with an extremely slow relaxing solvent coordinate and a fast relaxing intramolecular coordinate to describe the ET reactions.